(untitled) (Bangladesh Medical Journal Khulna, 2012)
Sixteen cases of old fracture neck femur were treated by internal fixation and anterior muscle pedicle bone grafting of rectus femoris, sartorius bone block from anterior superior iliac spine. The treatment period were from January 2000 to December 2009 at Khulna Medical College Hospital and some private hospital. Different methods of fixation and bone grafting procedure were reported. We did this procedure by open reduction and internal fixation by cannulated hip screws and muscle pedicle bone grafting. Additional cancellous bone grafting were done in every cases. Follow up period was 2 to 7 years (average 5 years). Evaluation parameter were union, non union. collapse of neck, avascular necrosis of femoral head (AVN) coxavara, shortening, pain, range of movement and functional activities and over all satisfaction of patient. The results of fracture healing rate was good (9), fair (4) and poor (3). The technique is simple, rewarding and easy access of fixation and muscle pedicle bone grafting. Bone graft was placed by making a gutter at fracture site and maintained by a screw or prolin suture. DOI: http://dx.doi.org/10.3329/bmjk.v43i1-2.13016 Bang Med J (Khulna) 2010; 43: 10-11